Luigi Gaffuri, "Racconto del territorio africano" (ENTHYMEMA, 2020)
Review of Gaffuri, Luigi. Racconto del territorio africano. Letterature per una geografia. Edizioni Lupetti, 2018.
Keywords: Territory; Landscape; Literary Geography; Depictions of Africa; Power.